Behavioural phenomena in persons with an intellectual developmental disorder according to the level of emotional development. Issue 5 (31st March 2022) - Hermann, H.; Berndt, N.; Lytochkin, A.; Sappok, T.
Abstract: Background: Challenging behaviours in people with an intellectual developmental disorder (IDD) are complex and often difficult to understand. The developmental perspective may provide additional insights into the specific behavioural patterns and underlying motives in different emotional reference ages. Methods: The behaviours of 185 adults with IDD who were admitted to psychiatry were systematically assessed with the Aberrant Behaviour Checklist (ABC) and the Modified Overt Aggression Scale (MOAS). The association of the different behaviours with various emotional reference age groups as assessed with the Scale of Emotional Development – Short (SED‐S) was analysed to deduce behavioural patterns typical for a certain level of functioning. Results: Overall, the severity of challenging behaviours decreases in higher emotional reference age groups. Physical aggression was most prevalent in persons in the second phase of emotional development (7–18 months reference age). In SED‐S‐1 (reference age 0–6 months), the persons appeared to be searching for physical comfort and showed high scores in social withdrawal, stereotypies and aggression towards the self. Persons functioning in SED‐S‐2 (reference age 7–18 months) scored highest in irritability and physical aggression ( searching for security ), while those in SED‐S‐3 (19–36 months) exhibited the searching for autonomy type characterised by defiant and socially inappropriate behaviours. Persons with an emotional reference age of 4–7 years (SED‐S‐4) showed inappropriate speech, verbal self‐regulation and depressive‐like behavioural aspects ( searching for identity ). Conclusions: The behavioural phenomena exhibited in a certain emotional reference age may support the clinician to differentiate behavioural problems from psychopathological symptoms to yield the proper diagnosis.